Caracterização do padrão de ondas superficiais de gravidade geradas pelo vento no complexo estuarino de são marcos (MA). - SANTOS, Erllen Dairlane Vieira (2018)
The study of the behavior of surface waves has become very relevant for many types of applications due to their great influence on the dynamics of coastal environments and offshore structures, as well as being one of the most important forms of energy transport in coastal environments. Because it is an area of high port activity, the study of the wave pattern in the Estuarine Complex of São Marcos is fundamental, since the knowledge of the possible impacts generated by the waves would reduce possible expenses and contribute to a better planning of the use and occupation of the coastal and port region. The objective of this study is to characterize the surface and gravity waves generated by the winds in the São Marcos Estuarine Complex. Through the use of ADCP's measurements were made of wave characteristics. The SW_LHiCEAI model simulated the Berkhoff experiment in order to validate its efficiency for wave propagation. The higher frequencies of the observed data indicated a higher incidence of waves coming from the Northwest, North and Northeast directions. However, this region has waves coming from all directions, which can be related to the large movement of ships that occurs because of the presence of the existing port complex in the CESM. The estuarine complex of São Marcos presented a very dynamic behavior regarding the waves. This is due to its geographical position, port presence and background configuration of this region that directly influence the waves.